Implementation of Drill Method to Improve Student Learning Outcomes in Islamic Education Learning Prayer Material at SD Negeri 101301 Rianiate Tapanuli Selatan - Batubara, Purnama (Journal of Indonesian Primary School, 2024)
The purpose of this study was to analyze the improvement of student learning outcomes in Islamic education learning by implementing the Drill Method at SD Negeri 101301 Rianiate. The research method used in this study was classroom action research. The subjects of the study were third grade elementary school students. Data were collected using test, observation and interview techniques. The results of the study were that the application of the Drill Method was very good because it could improve student learning outcomes in Islamic education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 48.71%, the first cycle 66.39% and in the second cycle it increased to 89.66%. Thus, the use of the drill method can be used as an alternative to improve student learning outcomes in Islamic education learning.